Nitrogênio em cobertura, teor de proteína e exportação de nutrientes pelos grãos de painço - Abrantes, Fabiana Lima [UNESP]; Kulczynski, Stela Maris; Soratto, Rogério Peres [UNESP]; Barbosa, Manoel Murilo Macedo (My University, 2011)
Knowledge of the mineral composition of grain and export of nutrients by the proso millet is important to enhance their use and promote more rational fertilizer recommendations. This work aimed to evaluate the protein and nutrients in the grain and export of macronutrient by the proso millet, cv. AL Tibagi, submitted to different doses and times of nitrogen top-dressing application. The experimental design was randomized block design in a 4×2 factorial scheme, constituted by four doses (0, 30, 60, and 120 kg ha -1 of N) and two application times (14 and 28 days after emergency) of N fertilizer (urea) in top-dressing with four replications. Nitrogen top-dressing application increased grain yield and N content and protein in grains of proso millet, however, reduced the concentration of K. Nitrogen topdressing fertilization increased the export of N, P, Ca, Mg and S for the grains of proso millet. Proso millet exported an average of macronutrients in the following order: 28.1 kg ha -1 N; 3.4 kg ha -1 P; 2.1 kg ha -1 Ca; 1.4 kg ha -1 S, 0.9 kg ha -1 K and 0.8 kg ha -1 Mg.
Top-dressing nitrogen fertilization, protein concentration and nutrients exportation by proso millet grains
Keywords: Chemical composition of the grains; Nitrogen fertilization; Panicum miliaceum L.; Time of application